UPAYA IBU DALAM PENATALAKSANAAN ANAK DENGAN ASMA DI RUMAH - sri winarni; Agus Khoirul Anam (Jurnal Pendidikan Kesehatan, 2020)
Problems and difficulties often faced by mothers in the treatment of children with asthma especially when at home, 76,5 percent of childrens with asthma for treatment because of house dust as the originator. The purpose of research is to describe the efforts of mothers in treatment of children with asthma at home. Methods in research using descriptive design. The population in this study are all of mothers children with asthma in the area of Health UPTD Sananwetan Blitar Town in 2015 as many as 69 people, and large samples used are as many as 30 people using purposive sampling technique. Data was collected be a questionnaire designed by the researchers. The results of this study show the mothers treatment generally good enough that amounted to 53.3 percent of mothers. In this study, especially the failure of the rehabilitative effort of mothers 86,6 percent rehabilitative effort are still lacking. Health workers need to provide health education on materal efforts in the management of children with asthma in the home, especially the introduction of rehabilitatif efforts.